The Effect of Lactobacillus acidophilus and Chito−Oligosaccharide on Antibacterial Activity and Organic Acid Production - Miksusanti Miksusanti; Harian Saputra; Sofia Sandi; Hermansyah Hermansyah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
The effect of Lactobacillus acidophilus combined with and without Chito-Oligosaccharide (COS) on the growth of Escherichia coli and Staphylococcus aureus had been studied. The antibacterial activity of L. acidophilus before and after combination with COS 0.2% was tested on bacteria of E. coli and S. aureus with well-diffusion method. Incubation time was carried out in 44, 46, 48, 50, and 52 hours. Organic acids produced by L. acidophilus bacteria was measured by HPLC. The result showed that COS 0.2% can inhibit the growth of E. coli and S. aureus 37.2 mm2 and 52 mm2 respectively. Combination of L. acidophilus and COS 0.2% gave inhibition zone larger than L. acidophilus without COS 0.2%. Incubation time within 48 hours of L. acidophilus combined with COS 0.2% produced the largest inhibition zone against E. coli and S. aureus 367.92 mm2 and 343.99 mm2 respectively. Optical density measurement resulted in higher value for combination one but concentration of organic acid produced was lower compare to L. acidophilus without COS 0.2%.Keywords: COS, L. acidophilus, Organic acid, antibacterial.